Talisman as an element of intangible heritage and commercialization of the sports event - E. A. Gureeva (Вестник Российского экономического университета имени Г. В. Плеханова)
The article studies the intangible heritage of sports event and, in particular, an official talisman of a sports competition as a carrier of cultural and commercial component. The goal of the research is to reveal the importance of the talisman of official competition for fans and estimate the demand for the product with the image of official talisman using the World Football Cup 2018 in Moscow as an example and at the same time to show profit from selling this type of product. The research was based on survey results aimed at identifying the demand for products with the event symbol. The author found out the following: 1. Expenses of fans from different countries on souvenir products with the event symbol were different; 2. Products with the event talisman were in the highest demand; 3. The total profit from selling souvenir products with the official talisman of the World Cup 2018 in Russia, Zabivaksa wolf made over €50m. As a conclusion the author provides recommendations on developing souvenir products with the official talisman of the event in order to maximize its cultural and commercial value. Key factors of the successful development of licensed products of sports competitions were shown.